Teachers' Perceptions of ELL Students: Do Their Attitudes Shape Their Instruction?. Issue 3 (3rd July 2017) - Carley Rizzuto, Kerry
ABSTRACT: The purpose of this parallel mixed-methodology study was to examine how the perceptions of early childhood teachers toward their early childhood English Language Learners (ELL) shape their pedagogical practices. The study was conducted in 10 early childhood classrooms, ranging from grades pre-K to third, in one suburban school with a culturally and linguistically diverse student population. Quantitative data was gathered through the administration of Pohan and Aguilar's (2001) Professional beliefs about diversity Likert scale. Additionally, qualitative data w`ere collected. Although some survey responses and interviews indicated that participants were aware of and accepting of all students' funds of knowledge and were eager to draw on their students' cultural backgrounds languages, most were ill-equipped or unwilling to differentiate their instruction for ELL students. Implications for inservice teacher professional development to gain understandings of the theories of second language acquisition and culturally responsive pedagogy are discussed.